"Digital Humanities" Reconsidered: Early Modern Latin Sources in Online Teaching - Walser-Bürgler, Isabella (The sixteenth century journal, 2020)
The article focuses on teaching Neo-Latin in an undergraduate seminar in Austria during the pandemic caused by COVID-19 and how the course highlighted constructivist learning and digital humanities. The author discusses Early Modern primary and secondary sources online and the advantages these online resources offer.